Productivity of cows and heifers of Ayrshire breed in conditions of Poltava region - Войтенко, А. М. (Scientific Progress & Innovations, 2017)
The analysis of the productivity of repair heifers and Ayrshire breed cows is conducted, which are bred in the conditions of Poltava with the possibility of increasing the genetic potential of animals taking into account a number of factors. It is determined that the herd contains bull daughters of 10 lines, which have different breed value, which causes the variability of economically useful signs of animals. Heifers are characterized by uneven growth with the most intensive increase in absolute and average daily growth in the period of twelve to eighteen months. It is proved that the cows of the Ayrshire breed, having an average milk yield of 305 days of lactation at a level of 6,460 kg, increase their milk yield with an increase in the number of lactations. On the background of a fairly high milk productivity of cows in the herd, there are serious problems with reproduction.